Peculiarities of Labour Income Taxation in the Baltic States - Ilona Skačkauskienė (Entrepreneurial Business and Economics Review, 2013)
The main objective of the paper is to analyse the peculiarities of the taxation of labour income in the Baltic States (Lithuania, Latvia and Estonia). The results of the research have shown that the comparison of the basic tax indicators, such as non-taxable minimum income and standard rates, only partially describe the national level of the labour income taxation. A more accurate description of the tax level could be provided only after applying ratios and evaluating such factors as tax base and tax exemptions.